2013
DOI: 10.1016/j.joen.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxyethyl Methacrylate Inhibits Migration of Dental Pulp Stem Cells

Abstract: Objectives Cell migration is an important step in pulpal wound healing. Although components in the resin-based dental materials are known to have adverse effects on pulp wound healing including proliferation and mineralization, their effects on cell migration have been scarcely examined. Here, we investigated effects of 2-Hydroxyethyl methacrylate (HEMA) on migration of dental pulp stem cells (DPSC) in vitro. Methods Cell viability was assessed using MTT assay, and cell migration was evaluated using wound sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…HEMA at a dose leading to a 20% reduction in cell viability inhibited the migration of human pulp cells and that this inhibitory effect increased with the HEMA concentration, consistent with previous findings (Williams et al . ). These findings suggest that HEMA inhibits the migration and differentiation of pulp cells into the odontoblast layer in vitro .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…HEMA at a dose leading to a 20% reduction in cell viability inhibited the migration of human pulp cells and that this inhibitory effect increased with the HEMA concentration, consistent with previous findings (Williams et al . ). These findings suggest that HEMA inhibits the migration and differentiation of pulp cells into the odontoblast layer in vitro .…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has proven that pulp cell migration can mediate different signalling pathways and that HEMA‐mediated inhibition of this migration is associated with the phosphorylation signalling proteins focal adhesion kinase and P38 (Williams et al . ). Increased phosphorylation of extracellular signal‐regulated kinase 1/2 has also been observed in HEMA‐treated cells (Spagnuolo et al .…”
Section: Discussionmentioning
confidence: 97%
“…Two-hydroxyethyl methacrylate (HEMA), a kind of resinbased dental materials, can inhibit the cell migration of dental pulp stem cells (DPSCs) by phosphorylation of p38 but not ERK, or JNK MAPK pathways [ 12 ]. p38 MAPK and insulin-like growth factor 1 receptor (IGF-1R) are responsible for the mitotic quiescence of DPSCs.…”
Section: Mapk Signaling Pathwaymentioning
confidence: 99%
“…MAPK regulates the directional migration of cells via the phosphorylation of MAPK-activated protein kinase 2/3 (MAPKAP 2/3). Some studies have demonstrated that HEMA inhibits the migration of DPSCs at non-toxic doses, and such inhibition is associated with the p38 signaling pathway [ 12 ]. Moreover, LPS can promote the adhesion and migration of DPSCs by upregulating the expression of adhesion molecules and chemotactic factors, while inhibition of MAPK and NF-κB signifi cantly antagonizes LPS-induced adhesion and migration [ 21 ].…”
Section: Mapk Signaling Pathwaymentioning
confidence: 99%
“…2-hydroxyethyl methacrylate (HEMA), a kind of resin-based dental materials, can inhibit the migration of DPSCs by phosphorylation of p38 or JNK MAPK pathways [99]. P38 MAPK and IGF-1R are responsible for the mitotic quiescence of DPSCs.…”
Section: Mapk Signaling Pathwaymentioning
confidence: 99%